Assessment of heavy metal contamination at west and east coastal area of peninsular Malaysia - Redzwan, Ghufran; Abdul Halim, H.; Alias, S.A.; Rahman, M.M. (Faculty of Science, University of Malaya, 2014)
Five heavy metal elements [Pb(II), Cr(VI), Ni(II), Zn(II) and Cu(II)] in the sediment of the two coastal areas had been analysed of the mid-east and mid-west of Peninsular Malaysia in the year of 2012. This is to assess and monitor contamination of heavy metal at mangrove area in the state of Negeri Sembilan, Melaka and Pahang. Overall and individual analyses on the heavy metals showed the concentration of the named heavy metals were not at alarming stage. All analysed elements were found to be much lower than the international guideline provided by the Chinese (EPA-China), Canadian (CEPA) and American (US-EPA). Quantitative assessment using Enrichment Factor shows that all analysed elements were to found be within the degree of background concentration.